Allyl isothiocyanate (AITC) induces stomatal closure in Arabidopsis - Md. Sarwar, Jahan (2011)
Isothiocyanates (ITCs) are degradation products of glucosinolates in crucifer plants and have repellent effect on insects. pathogens and herbivores. In this study, we report that exogenously applied ally! isothiocyanate (AITC) induced stomata! closure in Arabidopsis via production of reactive oxygen species (ROS) and nitric oxide (NO). and elevation of cytosolic Ca 2'. AITC-induced stomatal closures were partially inhibited by an inhibitor of NADPH oxidase and completely inhibited by glutathione monoethyl ester (GSHmee). AITC-induced stomata! closure and ROS production were examined in abscisic acid (ABA) deficient mutant aba2-2 and methyl jasmonate (MeJA)•deficient mutant aos to elucidate involvement of endogenous ABA and MeJA. Genetic evidences have demonstrated that AffC-induced stomata! closure required MeJA priming but not ABA priming. These results raise the possibility that crucifer plants produce ITCs to induce stomata! closure, leading to suppression of water loss and invasion of fungi through stomata. (g) 2011 Blackwell Publishing Ltd.